Calculation of temperature distribution and rheological properties of the lithosphere along Profile 1 passing through Aswan - RADWAN, Anwar H.; DÉREROVÁ, Jana; BIELIK, Miroslav; ŠIMONOVÁ, Barbora; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2017)
The 2D integrated geophysical modelling approach has been used to determine the temperature distribution in the lithosphere along the profile passing through Aswan. Based on the temperature model and the rheological parameters, we have calculated strength distribution in the lithosphere for the studied profile. The strength envelopes have been calculated for both compressional and extensional regimes. Our results indicate that the strength is constant along the whole length of the profile passing through the Nubia plain. The largest strength can be observed within the upper crust which allows us to assume rigid deformation in this part of the lithosphere, with compressional processes predominant. Towards the lower crust and upper mantle, strength values rapidly decrease for both regimes, suggesting ductile deformations in the lower part of the lithosphere.